Satire and Romanticism - Jones, S. author. aut Link
272 p.
Keywords: This remarkable study of the constructive and ultimately canon-forming relationship between satiric and Romantic modes of writing from 1760 to 1832 provides us with a new understanding of the historical development of Romanticism as a literary movement. Romantic poetry is conventionally seen as inward-turning, sentimental, sublime, and transcendent, whereas satire, with its public, profane, and topical rhetoric, is commonly cast in the role of generic other as the un-Romantic mode. This book argues instead that the two modes mutually defined each other and were subtly interwoven during the Romantic period. By rearranging reputations, changing aesthetic assumptions, and re-distributing cultural capital, the interaction of satiric and Romantic modes helped make possible the Victorian and modern construction of 'English Romanticism'.